2005
DOI: 10.1177/112067210501500128
|View full text |Cite
|
Sign up to set email alerts
|

Cystoid Macular Edema Associated with Latanoprost after Uncomplicated Cataract Surgery

Abstract: Until a causal relationship between CME and latanoprost is proved or disproved, caution in its use in pseudophakic patients would be prudent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 21 publications
0
22
0
6
Order By: Relevance
“…All of these patients were on Latanoprost 0.005% eye drops prior to surgery, which might be a risk factor for these complications. Latanoprost therapy enhances disruption of the blood-aqueous barrier and increases the incidence of angiographic CME [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…All of these patients were on Latanoprost 0.005% eye drops prior to surgery, which might be a risk factor for these complications. Latanoprost therapy enhances disruption of the blood-aqueous barrier and increases the incidence of angiographic CME [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Agange et al presented a case report of a glaucomatic patient who developed recurrent CME with three separate trials of three different prostaglandins after uncomplicated cataract surgery. Other studies have also reported same findings (Yeh & Ramanathan, 2002;Altintaş et al, 2005;Panteleontidis et al, 2010). In a study conducted in our institution, we prospectively examined macular thickness alterations after uncomplicated phacoemulsification in four different groups of patients.…”
Section: Incidence Epidemiology Risk Factorsmentioning
confidence: 67%
“…Mediator agents such as prostaglandins can cause leakage of perifoveal capillaries, which can lead to accumulation of fluid in the outer retinal layers [10,11]. However, postoperative CME may be seen as a result of persistent traction upon the fovea from an attached posterior hyaloid [12].…”
Section: Discussionmentioning
confidence: 99%